Characterization of cross‐linked gelatin nanoparticles by electrophoretic techniques in the liquid and the gas phase. Issue 24 (13th November 2013) - Weiss, Victor U.; Lehner, Angela; Kerul, Lukas; Grombe, Ringo; Kratzmeier, Martin; Marchetti‐Deschmann, Martina; Allmaier, Günter
<x xml:space="preserve">Abstract</x> Biodegradable nanoparticles (NPs) and hence, for example, NPs prepared from glutaraldehyde cross‐linked gelatin (gelatin NPs) are lately receiving increased attention in various fields such as pharmaceutical technology and nutraceutics as biocompatible carriers for hardly water soluble drugs, molecules intended for sustained release or targeted transport. However, in vivo application of such materials requires a thoroughly characterization of corresponding particles. In a previous manuscript, we demonstrated the applicability of chip electrophoresis for the separation of gelatin NPs from NP building blocks. Following our previous results, we intensified our efforts in the characterization of gelatin NPs by electrophoresis in the liquid (capillary and chip format) and the gas phase (gas phase electrophoretic mobility molecular analysis). In doing so, we demonstrated differences between nominally comparable (from the concentration of initially employed material for cross‐linking) gelatin NP preparation batches concerning (i) the amount of obtained NPs, (ii) the degree of NP cross‐linking, (iii) the amount of NP building blocks present within samples, and (iv) the electrophoretic mobility diameter of NPs. Differences were even more pronounced when NP preparations from batches with different content of initially employed gelatin were compared. Additionally, we compared three setups for the removal of low molecular weight components from samples after fluorescence labeling of NPs. In overall, the combination of the three employed analytical methods for gelatin NP characterization—CE in the capillary and the chip format as well as gas phase electrophoretic mobility molecular analysis—allows a more thoroughly characterization of NP containing samples.